Vegetative and reproductive plasticity of broccoli at three levels of incident photos ynthetically active radiation - Francescangeli, N.=700 1 Sangiacomo, M.A.; Marti, H.R.
(En, Es)
Ilus., 50 ref.
Keywords: BRAáICA OLERACEAE ITALICA; SUPERFICIE FOLIAR; CRECIMIENTO; RENDIMIENTO; ETAPAS DE DESARROLLO DE LA PLANTA; CONTENIDO DE MATERIA SECA; SOMBRA; ESPAÑA; BROCOLI